Zanthoxylum armatum DC. (Rutaceae) - An Endangered Tree from Chhattisgarh, Needs Conservation - Sikarwar, R.L.S.; Tiwari, Arjun Prasad; Shukla, Achuta Nand; Sikarwar, Pooja Singh (Indian Forester, 2023)
No Abstract.